Are the WHO guidelines on breastfeeding appropriate for India ? - Anandaiah, Ravilla; Choe, Minja Kim, 1941-; International Institute for Population Sciences; East-West Center. Population and Health Studies (Mumbai, India : International Institute for Population Sciences, 2000)
Reports summarize findings from India's National Family Health Survey conducted 1992-93.
Refrences: p. 22-23
Keywords: Breast feeding -- India; Breast feeding promotion -- India